Performance analysis of a wireless sensor network with cognitive radio capabilities in structural health monitoring applications: A discrete model - Hassel Aurora Alcalá Garrido; Mario E Rivero-Angeles; Eleazar Aguirre Anaya; Felipe A Cruz-Perez; S Lirio Castellanos-Lopez; Genaro Hernandez-Valdez (International Journal of Distributed Sensor Networks)
This article studies the performance of a wireless sensor network with cognitive radio capabilities to gather information about structural health monitoring of buildings in case of seismic activity. Since the use of the local area network is intensive in office and home environments, we propose the use of empty cellular channels (primary system). As such, the structural health monitoring does not degrade the local communications. Thus, the wireless sensor network for structural health monitoring acts as secondary network. Two discrete-time analytical approaches are proposed and developed to evaluate the system performance in terms of both the average packet delay and average energy consumption. The first one is an approximation suitable for the case when the time slot duration is small relative to the mean call inter-arrival time. The second model is accurate for any time slot duration and inter-arrival times.